2007
DOI: 10.1007/s00586-007-0512-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five specific scores for cervical spondylogenic myelopathy

Abstract: The ability to compare various results that measure clinical deficits and outcome is a necessity for successful worldwide discussion about cervical spondylogenic myelopathy (CSM) and its treatment. There is hardly any information in literature how to value and compare outcome assessed by different scores. In a retrospective study we objectively evaluated the Nurick-score, Japanese-orthopaedic-association-score (JOA-Score), Cooper-myelopathyscale (CMS), Prolo-score and European-myelopathy-score (EMS) using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 30 publications
4
79
1
5
Order By: Relevance
“…Interestingly, in our study, the variation in percentage of patients who showed an improvement in the Nurick grade, tmJOA and llmJOA scores was less, ranging from 78.5 to 94.6% for llmJOA and tmJOA scores, respectively, with the percentage of patients determined to have improved their Nurick grade being in between at 83.8%. Although Vitztum et al [12] found a significant difference in the mean postoperative recovery rates assessed by the Nurick grade (23%) and JOA scoring system (37%), the variation was less than that noted for the percentage of patients showing improvement in the different functional scales. Hence, they concluded that to enable comparison across studies that have used CSM specific functional scales, it is more appropriate to report the mean recovery rate rather than the proportion of patients showing an improvement in the functional scores.…”
Section: Correlation In Different Grades Of Myelopathymentioning
confidence: 81%
See 3 more Smart Citations
“…Interestingly, in our study, the variation in percentage of patients who showed an improvement in the Nurick grade, tmJOA and llmJOA scores was less, ranging from 78.5 to 94.6% for llmJOA and tmJOA scores, respectively, with the percentage of patients determined to have improved their Nurick grade being in between at 83.8%. Although Vitztum et al [12] found a significant difference in the mean postoperative recovery rates assessed by the Nurick grade (23%) and JOA scoring system (37%), the variation was less than that noted for the percentage of patients showing improvement in the different functional scales. Hence, they concluded that to enable comparison across studies that have used CSM specific functional scales, it is more appropriate to report the mean recovery rate rather than the proportion of patients showing an improvement in the functional scores.…”
Section: Correlation In Different Grades Of Myelopathymentioning
confidence: 81%
“…These two patients who had improved from Nurick grade 1 to 0 had no dysfunction on llmJOA preoperatively (score of 7). [12]. In a retrospective study of 43 patients with CSM who underwent anterior decompression, Vitztum et al [12] showed that there was good correlation between the preoperative and postoperative scores using the Nurick scale and JOA scoring system.…”
Section: Correlation In Different Grades Of Myelopathymentioning
confidence: 99%
See 2 more Smart Citations
“…However, few validated evaluation tools were available for CSM when the first patients evaluated in this series were treated. Moreover, the choice to use the recovery rate to evaluate the improvement obtained with surgery rather than the simple difference between preoperative and postoperative scores, enabled us to decrease the potential discrepancy between the Nurick score recorded in this study and the assessment that can be obtained using more recent validated tools [31]. Despite the above limitations, this study provides useful information on the long-term followup of patients undergoing the Cloward procedure, with important methodological strengths.…”
Section: Discussionmentioning
confidence: 99%